Catalytic cracking catalyst with high thermal wear resistance and preparation method thereof

By using a high shear emulsifier in the catalytic cracking catalyst to mix zeolite molecular sieve, matrix and modified binder, and perform spray molding and drying and ion exchange, the problem of insufficient anti-wear performance of the catalyst at high temperature is solved, and a higher level is achieved wear resistance and reaction properties.

CN119386924AActive Publication Date: 2025-02-07PETROCHINA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310922368.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-07
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

The existing catalytic cracking catalysts have insufficient wear resistance at high temperatures, resulting in abnormal fluidization, increased solid content of runners, hood scale and oil slurry, affecting the long-term operation of the catalyst.

Method used

Using a catalytic cracking catalyst containing phosphorus and zeolite, the zeolite molecular sieve, matrix and modified binder are mixed in a high shear emulsifier, spray molding and drying and calcining, and further ion exchange is carried out to improve the thermal wear resistance of the catalyst.

Benefits of technology

The wear resistance and reaction performance of the catalyst are significantly improved, ensuring the stability and efficiency of the catalyst for long-term operation at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004359028620000241
    Figure BDA0004359028620000241
  • Figure BDA0004359028620000251
    Figure BDA0004359028620000251
  • Figure BDA0004359028620000252
    Figure BDA0004359028620000252
Patent Text Reader

Abstract

The invention discloses a catalytic cracking catalyst with high thermal wear resistance and a preparation method thereof, the catalytic cracking catalyst comprises the following raw materials: a zeolite molecular sieve, a matrix and a binder, the matrix is composed of a gamma-alumina precursor with a peptizing index less than or equal to 50% and clay, the binder comprises a phosphorus-containing compound, an aluminum-containing compound and a binder modifier; the binder modifier comprises a polymeshed chelating ligand, a metal center ligand, alcohol and organic acid, and the metal center ligand contains at least two metal ions; the catalytic cracking catalyst is prepared in a high shear emulsifier. Compared with the existing catalytic cracking catalyst, the catalytic cracking catalyst containing phosphorus and zeolite provided by the invention has the advantages of higher abrasive resistance, large pore volume, high molecular sieve content, high solid content and excellent reaction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalytic cracking catalyst with high thermal wear resistance and a preparation method thereof. Background Art

[0002] The catalytic cracking process has become the most important process for heavy oil processing due to its significant advantages such as high heavy oil conversion efficiency, good product quality, non-hydrogenation and low operating pressure. However, as the quality of heavy oil becomes increasingly poor and heavy, the harmful impurities such as vanadium, nickel, alkali metals, alkaline earth metals, and alkaline nitrogen increase, and the amount of slag is also increasing, which makes it difficult to crack heavy oil, and more coke is generated on the catalyst and deactivates faster. Therefore, it is necessary to develop catalytic cracking catalysts with higher activity, stronger heavy oil conversion ability, stronger heavy metal resistance, and better coke selectivity.

[0003] To achieve the above purpose, it is necessary to increase the molecular sieve content in the catalytic cracking catalyst, or to increase the pore volume of the catalytic cracking catalyst. The preparation of a catalyst with a macroporous structure is a solution. In addition, the development of new catalytic cracking technology, such as short contact or ultra-short contact time and the development of olefin catalytic cracking technology, also requires a catalyst with a high molecular sieve content and / or a macroporous structure that matches it. The binder in the catalytic cracking catalyst can provide a certain heat capacity during the catalytic cracking reaction. At the same time, the performance of the binder directly affects the particle size, wear index, pore volume and other physical and chemical properties of the catalyst. Therefore, most of the current research on the catalyst is focused on the modification of the binder.

[0004] However, in the prior art, when the binder is adjusted to develop a catalytic cracking catalyst with higher activity, stronger heavy oil conversion ability, stronger heavy metal resistance and better coke selectivity, increasing the content of the active component molecular sieve and increasing the pore volume of the catalytic cracking catalyst often leads to a deterioration in the catalyst's anti-wear performance (especially thermal wear performance at high temperatures), and then problems such as fluidization abnormalities, catalyst leakage, chimney fouling, and increased solid content of the oil slurry occur, affecting the long-term operation of the catalytic cracking unit.

[0005] For example, Chinese patent document CN201680055564.2 discloses a method for preparing a fluid catalytic cracking catalyst additive composition using a new binder. The steps involve mixing an alumina source with water to form a slurry; adding a certain amount of P2O5 source to the alumina slurry; then stirring the slurry and reacting it under controlled temperature and time conditions to form an aluminum phosphate binder; adding zeolite, a certain amount of silica binder and a certain amount of clay to the aluminum phosphate binder; and spray drying the slurry to form catalyst additive particles. The catalyst additive composition contains about 35% to about 65% by weight of zeolite; about 0% to about 10% by weight of silica; about 15% to about 50% by weight of clay, and an aluminum phosphate binder, the aluminum phosphate binder containing about 2.5% to 5% by weight of amorphous or pseudo-boehmite alumina and about 7% to 15% by weight of phosphoric acid. However, the aluminum phosphate binder prepared by this method has limited improvement on catalyst strength, and the pore volume of the catalyst is low.

[0006] US Patent No. 4407730 discloses a catalyst carrier which is basically composed of a magnesium oxide-aluminum oxide-aluminum phosphate matrix after being calcined at 500°C for 10 hours. The average pore size of the carrier is 10-300 angstroms and the specific surface area is 100-350 m 2 / g, pore volume 0.3-1.5ml / g, wherein the magnesium oxide content is 0.5 to less than 10mol% or 25-75mol%, the aluminum oxide content is 2-90mol%, and the aluminum phosphate content is 3-95mol%. The preparation method of the catalyst carrier is to mix an aluminum nitrate aqueous solution with magnesium nitrate and an 85% phosphoric acid solution, then add ammonium hydroxide solution, precipitate under the condition of pH=9, filter, dry and roast at 500℃ for about 10h. The catalytic cracking catalyst prepared by mixing the catalyst carrier with zeolite has high gasoline selectivity and can be used as a catalyst for cracking high-metal content raw materials. In the document, magnesium oxide is added in the process of preparing the binder to capture the high-content metal ions in the raw materials, thereby achieving the effect of processing high metal content, but the introduction of metal ions in the binder forms a fixed crystalline phase with the aluminum phosphate binder. In the actual reaction, the binding performance of the binder is reduced due to the capture effect of magnesium ions. At the same time, the use of the aluminum phosphate binder will reduce the pore volume and specific surface area of ​​the catalyst, and it is easy to crack at high temperature, which makes its high-temperature wear resistance worse.

[0007] US Patent Document US5286369 discloses a catalytic cracking method for hydrocarbon raw materials, which comprises reacting a hydrocarbon raw material under catalytic cracking process conditions and in the presence of a catalyst, wherein the catalyst comprises a zeolite selected from ultrastable Y zeolite, ZSM-5 zeolite, Beta zeolite, SAPO zeolite, and ALPO zeolite and a crystalline aluminum phosphate binder, wherein the specific surface area of ​​the crystalline aluminum phosphate binder is less than 20 m2 / g and the pore volume is less than 0.1 ml / g. However, the specific surface area and pore volume of the crystalline aluminum phosphate binder in the method are relatively small, and the reaction performance of the catalyst finally obtained needs to be further improved.

[0008] Chinese patent document CN201110180891.X discloses an inorganic binder containing phosphorus aluminum compounds and a preparation method thereof, wherein the binder contains 15-40 wt% Al2O3, 45-80 wt% P2O5 and 1-40 wt% clay, wherein the P / Al weight ratio is 1-6, the pH value is 1-3.5, and the solid content is 15-60 wt%. The preparation method comprises: dispersing aluminum hydroxide and / or aluminum oxide and clay that can be colloided by acid with decationized water into a slurry with a solid content of 15-45 wt%, adding concentrated phosphoric acid to the slurry at a weight ratio of P / Al=1-6 under stirring, and then reacting at 50-99°C for 15-90 minutes. However, the binder prepared by the preparation method has a small pore volume and is easy to collapse at high temperature, and the catalyst prepared by the binder has poor thermal wear performance.

[0009] Chinese patent document CN99126287.5 discloses a catalytic cracking catalyst containing phosphorus and zeolite, which contains zeolite, clay and binder, wherein the catalyst also contains a phosphorus and aluminum additive uniformly dispersed in the catalyst, based on the total weight of the catalyst, the content of zeolite is 25-70 weight %, the content of clay is 5-55 weight %, the content of binder is 5-50 weight %, and the content of phosphorus and aluminum additive is 0.5-20 weight % based on the solid content of the additive. The phosphorus and aluminum additive is a reaction product obtained by reacting phosphoric acid solution with aluminum oxide and / or hydroxide, the specific gravity of which is 1.2-1.7 g / ml, and the atomic ratio of phosphorus to aluminum is greater than 1 to 12. However, this scheme still uses conventional binders to prepare catalytic cracking catalysts, and adds a small amount of aluminum phosphate binder. Due to the small amount added, the wear index of the catalyst cannot be significantly improved; at the same time, the phosphorus in the introduced aluminum phosphate additive exists in a free state, and migrates to the active center molecular sieve during the roasting process, destroying the molecular sieve structure and affecting the reaction performance; on the other hand, the colloidal particles of conventional binders such as aluminum sol and acidified pseudo-boehmite are small in size, filling the pores between the matrix and the active components, resulting in a small pore volume of the catalyst.

[0010] As mentioned above, the phosphate aluminum sol (or aluminum phosphate solution) used in the prior art is prepared by reacting a phosphorus compound with an aluminum sol or a silica sol under the condition of controlling pH>3; or, it is prepared by precipitating a phosphoric acid solution of aluminum nitrate and magnesium nitrate with an ammonium hydroxide solution under the condition of pH=9; or, it is prepared by precipitating a solution containing phosphoric acid and rare earth ions with an alkaline solution; or, it is prepared by precipitating a solution containing aluminum ions and phosphate and hydrogen phosphate with an alkaline solution; or, an ammonium salt selected from phosphoric acid, ammonium orthophosphate and ammonium salt of hypophosphoric acid and a phosphorus compound of phosphoric acid are directly added to a slurry containing silicon oxide, clay and zeolite; or, an aluminum phosphate solution with a pH of 0 to 1 is directly added to a slurry containing zeolite. When the catalyst is prepared by the above method, although the wear resistance of the catalyst can be increased to a certain extent, when the molecular sieve content in the catalyst is high or the catalyst pore volume is large, its wear resistance is still insufficient. At the same time, it is found that when the molecular sieve content in the catalyst is high or the catalyst pore volume is large, when the catalyst is prepared by the existing aluminum phosphate sol, the catalyst particles are broken to varying degrees, especially after high-temperature water vapor aging, the situation is worse. This is because when the phosphoric acid binder is prepared by the above method, the binder is mixed with the matrix material and the molecular sieve for a long time, and the matrix material and the molecular sieve contain more chlorine, ammonium, nitrate and various metal ions, resulting in impurities in the formed aluminum phosphate crystals. At high temperatures, especially in the presence of water vapor, the crystal structure is easy to collapse; the chlorine, ammonium and nitrate that are stably combined with the bonding component become unstable, and generate hydrogen chloride, ammonia, nitrogen, oxygen and other gases respectively. The generation of these gases generates a large number of "bubbles" inside the catalyst particles. When the temperature rises, these bubbles will rush out from the inside of the catalyst, resulting in damage to the shape of the catalyst particles. In severe cases, the catalyst particles are broken, thereby reducing the bonding effect of various binders and greatly reducing the anti-wear performance of the catalyst. Summary of the invention

[0011] In view of the problems existing in the prior art and the directions for improvement, the present invention provides a catalytic cracking catalyst with high thermal wear resistance and a preparation method thereof. Compared with the existing catalytic cracking catalysts, the phosphorus- and zeolite-containing catalytic cracking catalyst provided by the present invention has higher wear resistance, and at the same time has a large pore volume, a high molecular sieve content and excellent reaction performance.

[0012] To achieve the above object, the present invention provides the following technical solutions:

[0013] A catalytic cracking catalyst with high thermal wear resistance, wherein the raw materials of the catalytic cracking catalyst include zeolite molecular sieve, matrix and binder, wherein the matrix is ​​composed of a γ-alumina precursor with a peptization index of ≤50% and clay, and the binder includes a phosphorus-containing compound, an aluminum-containing compound and a binder modifier;

[0014] The binder modifier is composed of a multi-dentate chelating ligand, a coordinating metal, an alcohol and an organic acid, and the metal center ligand contains at least two metal ions;

[0015] The catalytic cracking catalyst is prepared in a high shear emulsifier.

[0016] Optionally, in the catalytic cracking catalyst provided by the present invention, the multidentate chelating ligand is a bidentate chelating ligand having at least two coordinating atoms, and the coordinating atoms are P, O or N, O; preferably, the multidentate chelating ligand is selected from any one of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediaminetetra (methylene phosphonic acid), diethylenetriaminepenta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, bis-1,6-hexamethylenetriaminepenta (methylene phosphonic acid), hexamethylenediaminetetra (methylene phosphonic acid), ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid and 1,2-ethylenediamine; more preferably, the coordinating atoms in the multidentate chelating ligand are P and O.

[0017] Optionally, in the catalytic cracking catalyst provided by the present invention, the metal ions in the metal center ligand are selected from rare earth metal ions and transition metal ions; preferably, the rare earth metal ions are selected from light rare earth metal ions; more preferably, the rare earth metal ions are selected from rare earth metal ions, such as one or more of lanthanum ions, cerium ions, neodymium ions, samarium ions, etc.; the transition metal ions are selected from one or more of copper, silver, nickel, zinc, cobalt, cadmium, etc. The metal center ligand is selected from chlorides or nitrates of rare earth metals and transition metals.

[0018] Optionally, in the catalytic cracking catalyst provided by the present invention, the dosage ratio of various metal ions in the metal center ligand is not specifically limited and can be adjusted according to actual conditions. The metal ions in the metal center ligand recommended by the present invention are selected from transition metal ions and rare earth metal ions, and the molar ratio of the transition metal ions to the rare earth metal ions is 1:5 to 10; the molar ratio of the multi-dentate chelating ligand to the metal ions in the metal center ligand is 2 to 5:1.

[0019] Optionally, in the catalytic cracking catalyst provided by the present invention, the organic acid is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid;

[0020] The alcohol is selected from C1-C3 monohydric alcohols, preferably one or more of methanol, ethanol and propanol.

[0021] Optionally, in the catalytic cracking catalyst provided by the present invention, the content of the binder modifier is 1% to 3%, based on the total mass of the catalytic cracking catalyst on a dry basis being 100%.

[0022] Optionally, in the catalytic cracking catalyst provided by the present invention, the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 4 to 10:1, and preferably the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 5 to 8:1. The aluminum-containing compound and the phosphorus-containing compound are not specifically limited, and conventional ones in the industry can be used. The aluminum-containing compound includes but is not limited to aluminum oxides, aluminum hydroxides, aluminum-containing organic compounds, etc., such as aluminum oxide, aluminum hydroxide, boehmite, sodium aluminate, aluminum chloride, aluminum isopropoxide, etc.; the phosphorus-containing compound includes but is not limited to phosphorus oxides, phosphorus oxyacids, phosphates, etc., such as phosphoric acid, diammonium hydrogen phosphate, phosphorus pentoxide, organic phosphonic acid, sodium phosphate, calcium phosphate, etc.

[0023] Optionally, in the catalytic cracking catalyst provided by the present invention, the peptization index of the γ-alumina precursor is 20% to 30%; preferably, the XRD spectrum of the γ-alumina precursor shows characteristic peaks near 2θ of 14±1°, 28±1°, 38±1°, and 49±1°, such as pseudo-boehmite, boehmite, boehmite, etc.

[0024] Optionally, in the catalytic cracking catalyst provided by the present invention, the mass ratio of the γ-alumina precursor to the clay is 1:1-9, preferably 1:3-7.

[0025] Optionally, in the catalytic cracking catalyst provided by the present invention, the clay in the matrix can be any clay commonly used in the art, which can meet the requirements of the present invention, such as one or more of kaolin, halloysite, montmorillonite, diatomaceous earth, bentonite, halloysite, etc., which are commonly used as components of catalytic cracking catalysts. Preferably, the clay is selected from kaolin, halloysite, halloysite or a mixture thereof.

[0026] Optionally, in the catalytic cracking catalyst provided by the present invention, the zeolite molecular sieves commonly used in the art can meet the requirements of the present invention. For example, it can be one or more of the various large-pore and medium-pore zeolite molecular sieves currently used as active components of catalytic cracking catalysts. Specifically, the zeolite molecular sieve can be selected from one or more of faujasite molecular sieves, ZSM series zeolite molecular sieves, Beta zeolite molecular sieves and mordenite molecular sieves.

[0027] Optionally, in the catalytic cracking catalyst provided by the present invention, based on the total dry weight of the catalytic cracking catalyst as 100%, the content of the zeolite molecular sieve is 25wt% to 60wt%, preferably 35wt% to 50wt%; the content of the matrix is ​​30wt% to 50wt%; the content of the binder is 10wt% to 25wt%, preferably 15wt% to 20wt%; and the solid content of the catalytic cracking catalyst is 35wt% to 60wt%, preferably 40wt% to 50wt%.

[0028] The method for preparing the catalytic cracking catalyst with high thermal wear resistance recommended by the present invention comprises the following steps:

[0029] The mixed slurry of the zeolite molecular sieve and the matrix is ​​mixed with the binder in a high shear emulsifier for 3 minutes, spray-formed, dried, calcined, and ion-exchanged to obtain the catalytic cracking catalyst with high thermal wear resistance.

[0030] By controlling the mixing time of the mixed slurry of zeolite molecular sieve and matrix with the prepared binder in the high shear emulsifier to be no more than 3 minutes, it is equivalent to achieving instantaneous and sufficient mixing, and immediately outputting and spray molding and drying after mixing, thus realizing the continuous process of "mixing, conveying, and drying and molding", avoiding the long-term contact between the mixed slurry and the binder, which would induce the migration of phosphorus, causing phosphorus to destroy the crystal structure and surface acid distribution of the molecular sieve, and at the same time make the bonding effect of the binder worse.

[0031] Optionally, in the method for preparing the above-mentioned catalytic cracking catalyst with high thermal wear resistance provided by the present invention, the mixed slurry of the zeolite molecular sieve and the matrix is ​​an operation well known in the art. Specifically, the zeolite molecular sieve, the matrix and deionized water are mixed and slurried without special requirements.

[0032] Optionally, in the method for preparing the above-mentioned catalytic cracking catalyst with high heat wear resistance provided by the present invention, the spray molding and drying refers to the granulation molding and drying of the material, which is a technology well known to those skilled in the art and can be carried out using existing parameters. For example, the preparation of catalytic cracking catalyst generally uses the following process conditions for spray molding and drying: the furnace temperature of the spray tower is controlled at 450-600°C, and the spray exhaust gas temperature is controlled at 150-300°C.

[0033] Optionally, in the method for preparing the catalytic cracking catalyst with high thermal wear resistance provided by the present invention, the ion exchange step is used to remove various impurity ions introduced in various links during the preparation process, including Na + , SO 4- , Cl -The ion exchange process conditions recommended by the present invention are: the ion exchange adopts acid exchange or ammonium exchange, the pH value is 3.0-3.5, and the exchange time is 0.3-2 hours.

[0034] Optionally, in the method for preparing a catalytic cracking catalyst with high thermal wear resistance provided by the present invention, the preparation of the binder comprises the following steps:

[0035] Adding alcohol to the organic acid solution of the multi-dentate chelating ligand and mixing well to obtain a multi-dentate chelating ligand solution;

[0036] Adding alcohol to the organic acid solution of the metal center ligand and mixing well to obtain a metal center ligand solution;

[0037] Adding the multi-dentate chelating ligand solution and the metal center ligand solution into a high shear dispersing emulsifier, adjusting the pH value of the system to 5-8, to obtain a binder modifier solution;

[0038] After heating an aqueous solution of a phosphorus-containing compound with a pH value of ≤5 to 60-80°C, adding an aluminum-containing compound to mix, then adding the mixed solution to a high shear emulsifier, reacting at 60-80°C to obtain a phosphorus-aluminum binder, adding the binder modifier solution to continue reacting at 60-80°C in a high shear emulsifier, and after the reaction is completed, the binder is obtained.

[0039] Optionally, in the preparation step of the binder provided by the present invention, the aqueous solution of the phosphorus-containing compound with a pH value of ≤5 is obtained by fully dissolving the phosphorus-containing compound with deionized water and then adjusting the pH with an acid. The acid is not specifically limited, and the inorganic acid, organic acid, etc. commonly used in this field can meet the requirements. Preferably, the pH of the aqueous solution of the phosphorus-containing compound is ≤3. However, when the phosphorus-containing compound is a phosphorus-containing organic acid or inorganic acid, no or a small amount of acid may be added according to the actual situation of the slurry to ensure that the pH value is within this range.

[0040] The specific preparation method of the above-mentioned catalytic cracking catalyst with high thermal wear resistance recommended by the present invention comprises the following steps:

[0041] S1: After clay, γ-alumina precursor and deionized water are mixed and homogenized, acid is added, and the slurry temperature is maintained at 40-80°C for acidification and peptization to prepare a matrix slurry;

[0042] S2: mixing the multidentate chelating ligand with the organic acid solution to prepare an organic acid solution of the multidentate chelating ligand, adding the alcohol solution, and mixing them evenly to obtain a multidentate chelating ligand solution (preferably, the molar concentration of the multidentate chelating ligand solution is 0.2-1.0 mol / L, the concentration of the organic acid is 10%-30%, and the concentration of the ethanol is 5%-20%);

[0043] S3: adding the metal center ligand to the organic acid solution, adding the alcohol solution after it is completely dissolved, and mixing evenly to obtain the metal center ligand solution; (preferably, the concentration of the organic acid is 10% to 30%, and the concentration of the ethanol is 5% to 20%);

[0044] S4: adding the multi-dentate chelating ligand solution into a high shear dispersing emulsifier, maintaining the temperature at 30-50° C., adding an equal volume of the metal center ligand solution, and adjusting the pH value of the system to 5-8; the molar ratio of the multi-dentate chelating ligand in the multi-dentate chelating ligand solution to the metal ion in the metal center ligand solution is 2-5:1. After the reaction is completed, a multi-metal composite chelating modifier solution is obtained;

[0045] S5: After heating the aqueous solution of the phosphorus-containing compound with a pH value of ≤5 to 60-80°C, adding the aluminum-containing compound to mix, and then adding the mixed solution into a high shear emulsifier to react at 60-80°C to obtain a phosphorus-aluminum binder, adding the binder modifier solution to continue reacting at 60-80°C in the high shear emulsifier, and after the reaction is completed, the binder is obtained.

[0046] S6: Add the matrix slurry obtained in S1 into a high shear emulsifier, add the pre-mixed molecular sieve slurry (the pre-mixed molecular sieve slurry is formed by mixing the molecular sieve with deionized water) after homogenization, mix evenly to obtain a mixed slurry; preferably, the mixing time of the mixed slurry of the zeolite molecular sieve and the matrix and the binder in the high shear emulsifier is not more than 3 minutes.

[0047] S7: spray forming, drying, calcining, and ion exchange to obtain the catalytic cracking catalyst with high thermal wear resistance.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] Beneficial effect 1: The catalytic cracking catalyst provided by the present invention adopts an in-situ prepared multi-metal chelate as a modifier to modify the aluminum phosphate binder, and the obtained modified binder replaces the aluminum sol, silica sol, acidified pseudo-boehmite and other binders in the existing catalyst. The aluminum phosphate binder is modified by the in-situ prepared multi-metal chelate, which can not only prevent the high content of binder from clogging the pores in the catalyst during the catalyst preparation process; but also reduce the amount of acid added during the catalyst preparation process, increase the pH value of the slurry, and thereby reduce the acid corrosion to the zeolite molecular sieve structure and improve the catalyst activity.

[0050] In the catalytic cracking catalyst provided by the present invention, a low peptization index γ-alumina precursor is used in the matrix. First, it can reduce the peptization of the γ-alumina precursor by the acidic medium during the catalyst preparation process, thereby reducing the peptized alumina blocking the pores of the catalyst and the pores of the zeolite molecular sieve, and accurately control the presence of free metallic aluminum in the catalyst system to avoid excessive reaction with the effective components of the binder, affecting the bonding performance of the binder, and the peptized small part of the γ-alumina precursor can react with the phosphorus-containing compound in the binder under specific conditions to form a binder. Second, the γ-alumina precursor with a low peptization index can form a large number of mesopores during the catalyst curing process, thereby increasing the pore volume of the catalyst. Third, the use of a low peptization index γ-alumina precursor can break the limitation that the solid content of the catalyst cannot be increased. The viscosity of the catalyst slurry can be adjusted by controlling the peptization solubility, greatly increasing the solid content of the catalyst slurry, which is of great significance for improving the sphericity of the catalyst.

[0051] The catalytic cracking catalyst provided by the present invention can maintain excellent abrasion resistance under the premise of high molecular sieve content and large pore volume by the mutual coordination between the components and the use of a high shear emulsifier to disperse the components during the preparation process.

[0052] Beneficial effect 2: In the binder of the catalytic cracking catalyst provided by the present invention, a metal-centered ligand composed of a multi-dentate chelate ligand and a plurality of metals is introduced. Under the promotion of organic acids and alcohols, a multi-metal chelate modifier can be prepared in situ during the preparation of the binder. Compared with directly using commercially available metal chelates, the in-situ prepared multi-metal chelate modifier has better water solubility, can promote the combination of the modifier and the phosphorus aluminum sol, and has a better modification effect; on the other hand, the use of multi-dentate chelate ligands can be chelated with a variety of metal ions to form a multi-metal chelate ligand, reducing the dissolution problem between different solvents during the preparation of the binder, and reducing the interaction between different chelate ligands; at the same time, the ratio of different metals can be flexibly controlled to achieve the effect of accurately regulating the performance of the binder; again, the method of in-situ preparation of a multi-metal chelate modifier can break the limitation of the small number of commercially available metal chelates and expand the applicability of binder preparation. Finally, it is preferred to use a multi-dentate chelate ligand with N, P, and O as the coordinating atoms to reduce the introduction of too many heteroatoms into the binder, affecting the performance of the binder, and reducing the impact on the performance of the catalyst.

[0053] Beneficial effect 3: In the binder of the catalytic cracking catalyst provided by the present invention, an in-situ prepared multi-metal chelate modifier is introduced to improve the properties of the phosphate binder. The transition metal ions and light rare earth metal ions in the multi-metal chelate can strengthen the interaction between aluminum phosphate and the matrix and improve the strength. Experiments show that the modification of the composite metal ions can greatly improve the thermal collapse phenomenon under high-temperature hydrothermal conditions and significantly improve the thermal wear performance of the catalyst; at the same time, it can avoid the premature hardening of the colloid during the catalyst molding and drying process, and increase the pore volume of the binder after curing. A large number of test results show that the addition of the multi-metal chelate modifier can form micropores and mesopores inside the binder during the preparation process without affecting the bonding performance of the binder.

[0054] Beneficial effect 4: The preparation method of the catalytic cracking catalyst provided by the present invention adopts a high shear emulsifier in the catalyst preparation process. On the one hand, the γ-alumina precursor with a low peptization index can be dispersed into a uniform and viscous emulsion slurry, and efficiently mixed with the zeolite molecular sieve, thereby overcoming the technical difficulty that the γ-alumina precursor with a low peptization index has poor solubility and cannot form a uniform slurry; at the same time, the γ-alumina precursor exists in a non-free state to avoid the transition reaction with the phosphorus-containing compound in the binder. On the other hand, the application of the high shear emulsifier solves the problem that the metal chelate formed in situ cannot be fully mixed with the aluminum phosphate binder, promotes the mutual reaction between the aluminum phosphate binder and the metal chelate, effectively regulates the microenvironment such as the supersaturation distribution in the reactor, and improves the role of the multi-metal chelate of the binder modification component. More importantly, the application of high shear emulsifier achieves efficient mixing of binder, molecular sieve and matrix mixed slurry in a short time, emulsifies the low peptization index γ-alumina precursor in a short time, and fully homogenizes the binder and the mixed slurry; after uniform mixing, spray drying is immediately carried out to avoid phosphorus migration caused by long-term contact between binder and molecular sieve, and achieves the encapsulation and positioning of phosphorus in aluminum phosphate binder. It plays an irreplaceable role in improving the reaction performance of the catalyst. DETAILED DESCRIPTION

[0055] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0056] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0057] The raw materials and equipment involved in the present invention are all commercially available and can meet the implementation of the technical solution of the present invention. However, for the convenience of comparison, the following raw materials are used in the following examples:

[0058] ReY molecular sieve, ultra-stable Y molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, and aluminum sol were collected from Lanzhou Petrochemical Company;

[0059] Phosphoric acid, aluminum hydroxide, diammonium hydrogen phosphate, aluminum chloride, phosphonic acid, phosphorus pentoxide, sodium aluminate, sodium phosphate, aluminum isopropoxide, hexamethylenediaminetetramethylenephosphonic acid, benzoic acid, 1-propanol, nickel nitrate, neodymium sulfate, lactic acid, cobalt chloride, samarium chloride, 1,2-ethylenediamine, ethylenediaminetetraacetic acid, hydroxyethylidene diphosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), formic acid, acetic acid, ethanol, copper nitrate, lanthanum chloride, silver nitrate, cerium nitrate, propionic acid, methanol, zinc sulfate, ethylenediaminetetraacetic acid chelated copper, hydroxyethylethylenediaminetriacetic acid chelated lanthanum; all are analytically pure and produced by Sinopharm Group;

[0060] Pseudo-boehmite, boehmite and boehmite are produced by China Aluminum Shandong Aluminum Co., Ltd.

[0061] Evaluation and analysis methods:

[0062] The surface area of ​​the catalyst was determined by low-temperature nitrogen adsorption-desorption method (NB / SH / T 0959);

[0063] The pore volume of the catalyst was tested using the water drop method (NB / SH / T 0955);

[0064] The catalyst wear index was determined using the straight tube method (NB / SH / T 0964);

[0065] The thermal collapse rate of the catalyst was tested on a laboratory small fixed fluidized bed (all parts are made of stainless steel) wear system. The specific steps are as follows:

[0066] The catalyst in the fluidized bed is constantly fluidized and worn under the action of fluidized air. The extremely fine powder particles under wear flow out of the fluidized bed through the filter element with the gas, while the larger particles are blocked by the filter element and remain in the fluidized bed to continue to wear. There are 5 air inlet holes evenly distributed at the front end and around the air guide tube, with an aperture of 1mm, and the filtration accuracy of the filter element is 1μm. During the experiment, first weigh 100g of the prepared catalyst, recorded as w1, and then add it to the fluidized bed, heat the preheater to 150℃, the fluidized bed temperature to 200℃, turn on the air generator, adjust the gas flow rate to 40m / s, and the apparent gas velocity in the reactor to 0.8m / s. After 4h of fluidized wear, weigh the remaining catalyst mass in the reactor and record it as w2, change the preheater temperature to 650℃, the fluidized bed temperature to 680℃, and repeat the measurement of the remaining catalyst weight under other conditions unchanged, recorded as w3, then the thermal collapse rate L is:

[0067] L=(w2-w3) / w2×100%

[0068] The catalyst reaction performance was tested on a small fixed fluidized bed microreactor according to the NB / SH / T0952-2017 method.

[0069] Example 1

[0070] The catalytic cracking catalyst provided in this embodiment, based on the total weight of the catalytic cracking catalyst on a dry basis as 100%, based on the solid content of the catalytic cracking catalyst slurry being 35wt%, has a ReY molecular sieve content of 25wt%, a boehmite (peptization index is 0) content of 25wt%, a kaolin content of 25wt%, and a binder content of 25wt%.

[0071] The molar ratio of phosphorus element to aluminum element in the binder is 4:1, the phosphorus-containing compound is phosphoric acid, and the aluminum-containing compound is aluminum hydroxide. The content of the binder modifier in the binder is 1.25wt% (based on the total mass of the catalyst dry basis as 100%), the multi-dentate chelating ligand in the binder modifier is 1,2-ethylenediamine, the organic acid is formic acid, the alcohol is ethanol, the transition metal ion compound is copper nitrate, the rare earth metal ion compound is lanthanum chloride, and the molar ratio of copper ion to lanthanum ion is 1:5.

[0072] Preparation of matrix slurry:

[0073] After kaolin, boehmite (peptization index is 0) and deionized water are mixed and homogenized, a small amount of hydrochloric acid is slowly added, and the slurry temperature is raised and maintained at about 45°C for acidification and peptization to prepare a matrix slurry.

[0074] Preparation of Binder Modifier:

[0075] S1: Mixing bidentate chelating ligand 1,2-ethylenediamine with formic acid solution to prepare bidentate chelating ligand organic acid solution, adding ethanol solution after mixing evenly to prepare 1,2-ethylenediamine ligand solution; wherein the molar concentration of 1,2-ethylenediamine in the solution is 0.2 mol / L, the concentration of organic acid is 30%, and the concentration of ethanol is 20%.

[0076] S2: Add lanthanum chloride and copper nitrate to formic acid solution, add ethanol solution after they are completely dissolved, and mix them evenly to obtain a mixed metal center ligand precursor solution. The concentration of formic acid in the precursor solution is 30%, the concentration of ethanol is 20%, and the molar concentration of the mixed metal in the precursor solution is 0.1 mol / L.

[0077] S3: Add the 1,2-ethylenediamine ligand solution obtained in S1 and the metal-containing center ligand precursor solution obtained in S2 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 50°C, add ammonia water to adjust the pH value of the system to 8, and react for 30 minutes to obtain a multi-metal composite chelating modifier solution.

[0078] Preparation of binder:

[0079] Concentrated phosphoric acid (concentration 85%) was diluted with deionized water to 40wt%, and then aluminum hydroxide was added in proportion and stirred at 80°C until completely dissolved, and the pH value was controlled to be 1.0. Then, the mixture of phosphoric acid and aluminum hydroxide was added to a high shear emulsifier, and the reaction temperature was maintained at 80°C for rapid reaction for 10 minutes, and then the previously prepared binder modifier was added in proportion, and the temperature was maintained to continue the reaction for 5 minutes to obtain a binder.

[0080] Preparation of catalytic cracking catalyst

[0081] The matrix slurry is added into a high shear emulsifier, and after homogenization, the pre-mixed molecular sieve slurry (molecular sieve is mixed with deionized water to form molecular sieve slurry) is added. The mixed slurry of the above binder, the zeolite molecular sieve and the matrix is ​​added into a high-speed shear emulsifier, and immediately discharged after high-speed emulsification for 2 minutes, and spray-formed and dried. The spray-formed conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray tail gas temperature is controlled at 160°C. The obtained material is calcined at 450°C for 1 hour, and then ion exchange is carried out for 0.5 hour with an ammonium chloride solution with a pH value of 3.0 to 3.5 to obtain a catalytic cracking catalyst.

[0082] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0083] Example 2

[0084] The catalytic cracking catalyst provided in this embodiment, based on the total weight of the catalytic cracking catalyst on a dry basis as 100%, based on the solid content of the catalytic cracking catalyst slurry as 50wt%, has a ReY molecular sieve content of 60wt%, a boehmite content of 3wt% (peptization index of 50%), a kaolin content of 27wt%, and a binder content of 10wt%.

[0085] The molar ratio of phosphorus element to aluminum element in the binder is 10:1, the phosphorus-containing compound is diammonium hydrogen phosphate, and the aluminum-containing compound is aluminum chloride. The content of the binder modifier in the binder is 2.0wt% (based on the total mass of the catalyst dry basis as 100%), the multi-dentate chelating ligand in the binder modifier is a hexadentate chelating ligand ethylenediaminetetraacetic acid, the organic acid is acetic acid, the alcohol is ethanol, the transition metal ion compound is silver nitrate, the rare earth metal ion compound is cerium nitrate, and the molar ratio of silver ion to cerium ion is 1:10.

[0086] The preparation method of the above catalytic cracking catalyst is as follows:

[0087] Preparation of matrix slurry:

[0088] Kaolin, boehmite (peptization index is 50%) and deionized water are mixed and homogenized, and then a small amount of hydrochloric acid is slowly added. The temperature of the slurry is raised and maintained at about 75° C. to perform acidification and peptization to prepare a matrix slurry.

[0089] Preparation of Binder Modifier:

[0090] S1: Mixing a hexadentate chelating ligand ethylenediaminetetraacetic acid with an acetic acid solution to prepare an acetic acid solution of an ethylenediaminetetraacetic acid multidentate chelating ligand, and adding an ethanol solution after mixing evenly to prepare an ethylenediaminetetraacetic acid ligand solution, wherein the molar concentration of the ethylenediaminetetraacetic acid is 1 mol / L, the concentration of the organic acid in the solution is 10%, and the concentration of the ethanol is 5%.

[0091] S2: Add cerium nitrate and silver nitrate to acetic acid solution, add ethanol solution after they are completely dissolved, mix well to obtain a mixed metal center ligand precursor solution. The concentration of acetic acid in the precursor solution is 10%, the concentration of ethanol is 5%, and the molar concentration of the mixed metal in the precursor solution is 0.2 mol / L.

[0092] S3: Add the ethylenediaminetetraacetic acid ligand solution obtained in S1 and the metal center ligand precursor solution obtained in S2 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 30°C, add ammonia water to adjust the pH value of the system to 5, and react for 50 minutes to obtain a multi-metal composite chelating modifier solution.

[0093] Preparation of the binder: Dissolve diammonium hydrogen phosphate with deionized water, adjust the pH to 5.0 with hydrochloric acid, heat to 60°C, then add aluminum chloride in proportion and stir until completely dissolved, then add the mixed solution into a high shear emulsifier, and keep the reaction temperature at 60°C for rapid reaction for 10 minutes, then add the previously prepared binder modifier in proportion, and continue to react at 60°C for 5 minutes to obtain the binder.

[0094] Preparation of catalytic cracking catalyst:

[0095] At room temperature, the matrix slurry is added to a high shear emulsifier, and after homogenization, the pre-mixed molecular sieve slurry is added. The mixed slurry of the above-mentioned binder, the zeolite molecular sieve and the matrix is ​​added to a high-speed shear emulsifier, and immediately discharged after high-speed emulsification for 2 minutes, and spray-formed and dried. The spray-forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray tail gas temperature is controlled at 160°C. After the obtained material is calcined at 450°C for 1 hour, it is ion-exchanged with an ammonium sulfate salt solution with a pH value of 3.0 to 3.5 for 0.3 hour to obtain a catalytic cracking catalyst.

[0096] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0097] Example 3

[0098] The catalytic cracking catalyst provided in this embodiment, based on the total weight of the catalytic cracking catalyst on a dry basis as 100%, based on the solid content of the catalytic cracking catalyst slurry as 40wt%, the content of ReY molecular sieve is 40wt%, the content of Beta molecular sieve is 10wt%, the content of pseudo-boehmite is 8.75wt% (peptization index is 20%), the content of halloysite is 26.25wt%, and the content of binder is 15wt%.

[0099] The molar ratio of phosphorus element to aluminum element in the binder is 5:1, the phosphorus-containing compound is an organic phosphonic acid (concentration 80%), and the aluminum-containing compound is aluminum hydroxide. The content of the binder modifier in the binder is 3.0wt% (based on the total mass of the catalyst dry basis as 100%), the multi-dentate chelating ligand in the binder modifier is a tetradentate chelating ligand hydroxyethylidene diphosphonic acid, the organic acid is propionic acid, the alcohol is methanol, the transition metal ion compound is zinc sulfate, the rare earth metal ion compound is neodymium sulfate, and the molar ratio of zinc ion to neodymium ion is 1:6.

[0100] The preparation method of the above catalytic cracking catalyst is as follows:

[0101] Preparation of matrix slurry:

[0102] Halloysite, pseudo-boehmite (peptization index is 20%) and deionized water are mixed and homogenized, and then a small amount of hydrochloric acid is slowly added. The temperature of the slurry is raised and maintained at about 50° C. to perform acidification and peptization to prepare a matrix slurry.

[0103] Preparation of Binder Modifier:

[0104] S1: Mix the tetradentate chelating ligand hydroxyethylidene diphosphonic acid with the propionic acid solution to prepare the propionic acid solution of the hydroxyethylidene diphosphonic acid multidentate chelating ligand, add the methanol solution after mixing evenly to prepare the hydroxyethylidene diphosphonic acid ligand solution, wherein the molar concentration of the hydroxyethylidene diphosphonic acid is 0.6 mol / L, the concentration of the organic acid in the solution is 20%, and the concentration of the methanol is 10%.

[0105] S2: Add neodymium sulfate and zinc sulfate to propionic acid solution, add methanol solution after they are completely dissolved, mix well to obtain a mixed metal center ligand precursor solution. The concentration of propionic acid in the precursor solution is 20%, the concentration of methanol is 10%, and the molar concentration of the mixed metal in the precursor solution is 0.2 mol / L.

[0106] S3: Add the hydroxyethylidene diphosphonic acid ligand solution obtained in S1 and the metal center ligand precursor solution obtained in S2 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.

[0107] Preparation of binder:

[0108] The organic phosphonic acid was diluted with deionized water to a concentration of 60%, and then aluminum hydroxide was added in proportion and stirred at 60°C until completely dissolved. The pH value of the system was adjusted to 2.0, and then the mixed solution was added to a high shear emulsifier, and the reaction temperature was maintained at 60°C for a rapid reaction for 10 minutes, and then the previously prepared binder modifier was added in proportion, and the reaction was continued at 60°C for 5 minutes to obtain a binder.

[0109] Preparation of catalytic cracking catalyst:

[0110] At room temperature, the matrix slurry is added to a high shear emulsifier, and after homogenization, the pre-mixed molecular sieve slurry is added to obtain a mixed slurry of the zeolite molecular sieve and the matrix. The above-mentioned binder and the mixed slurry of the zeolite molecular sieve and the matrix are added to the high shear emulsifier, and immediately discharged after high-speed emulsification for 2 minutes, and spray-formed and dried. The spray-forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray tail gas temperature is controlled at 160°C. After the obtained material is roasted at 450°C for 1 hour, it is ion-exchanged with an ammonium nitrate salt solution with a pH value of 3.0-3.5 for 0.3 hour to obtain a catalytic cracking catalyst.

[0111] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0112] Example 4

[0113] The catalytic cracking catalyst provided in this embodiment, based on the total weight of the catalytic cracking catalyst on a dry basis as 100%, based on the solid content of the catalytic cracking catalyst slurry as 60wt%, the content of ReY type molecular sieve is 30wt%, the content of ZSM-5 molecular sieve is 5%, the γ-alumina precursor is boehmite, and the content of boehmite is 5.6% (the peptization index is 30%); the content of halloysite is 39.4wt%, and the content of the binder is 20wt%.

[0114] The molar ratio of phosphorus element to aluminum element in the binder is 8:1, the phosphorus-containing compound is phosphorus pentoxide, and the aluminum-containing compound is sodium aluminate. The content of the binder modifier in the binder is 3.0wt% (based on the total mass of the catalyst dry basis as 100%), the multi-dentate chelating ligand in the binder modifier is a tetradentate chelating ligand hexamethylenediaminetetramethylenephosphonic acid, the organic acid is benzoic acid, the alcohol is 1-propanol, the transition metal ion compound is nickel nitrate, the rare earth metal ion compound is neodymium sulfate, and the molar ratio of nickel ion to neodymium ion is 1:5.

[0115] The preparation method of the above catalytic cracking catalyst is as follows:

[0116] Preparation of matrix slurry:

[0117] Boehmite (peptization index of 30%), argonite and deionized water are mixed and homogenized, and then a small amount of hydrochloric acid is slowly added. The temperature of the slurry is raised and maintained at about 60° C. to perform acidification and peptization to prepare a matrix slurry.

[0118] Preparation of Binder Modifier:

[0119] S1: Mixing a tetradentate chelating ligand hexamethylenediaminetetramethylenephosphonic acid with a benzoic acid solution to prepare a benzoic acid solution of a hexamethylenediaminetetramethylenephosphonic acid multidentate chelating ligand, and adding an ethanol solution after mixing evenly to prepare a hexamethylenediaminetetramethylenephosphonic acid ligand solution, wherein the molar concentration of the hexamethylenediaminetetramethylenephosphonic acid is 0.6 mol / L, the concentration of the organic acid in the solution is 20%, and the concentration of the ethanol is 10%.

[0120] S2: Add nickel nitrate and neodymium sulfate to benzoic acid solution, add 1-propanol solution after complete dissolution, mix well to obtain mixed metal center ligand precursor solution. The concentration of benzoic acid in the precursor solution is 20%, the concentration of 1-propanol is 10%, and the molar concentration of mixed metals in the precursor solution is 0.2 mol / L. S3: Add the hexamethylenediaminetetramethylenephosphonic acid ligand solution obtained in S1 and the metal center ligand precursor solution obtained in S2 to a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, react for 40 minutes, and obtain a multi-metal composite chelating modifier solution.

[0121] Preparation of the binder: Phosphorus pentoxide is slurried and mixed evenly with deionized water, and stirred at 80°C until completely dissolved, and the pH is adjusted to 1.5 with hydrochloric acid, and then sodium aluminate is added in proportion, and stirred until completely dissolved. The mixed solution is added to a high shear emulsifier, and the reaction temperature is maintained at 80°C for rapid reaction for 10 minutes, and then the previously prepared binder modifier is added in proportion, and the reaction is continued at 80°C for 5 minutes to obtain the binder.

[0122] Preparation of catalytic cracking catalyst:

[0123] At room temperature, the matrix slurry is added to a high shear emulsifier, and after homogenization, the pre-mixed molecular sieve slurry is added to obtain a mixed slurry of the zeolite molecular sieve and the matrix. The above-mentioned binder and the mixed slurry of the zeolite molecular sieve and the matrix are added to the high shear emulsifier, and immediately discharged after high-speed emulsification for 4 minutes, and spray-formed and dried. The spray-forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray tail gas temperature is controlled at 160°C. After the obtained material is roasted at 450°C for 1 hour, it is ion-exchanged with an ammonium carbonate solution with a pH value of 3.0 to 3.5 for 0.3 hours to obtain a catalytic cracking catalyst.

[0124] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0125] Example 5

[0126] The catalytic cracking catalyst provided in this embodiment, based on the total weight of the catalytic cracking catalyst on a dry basis as 100%, based on the solid content of the catalytic cracking catalyst slurry being 45wt%, the content of the ultra-stable Y molecular sieve is 42wt%, the γ-alumina precursor is pseudo-boehmite, the content of the pseudo-boehmite is 6.7% (peptization index is 25%), the content of montmorillonite is 33.3%, and the content of the binder is 18wt%.

[0127] The molar ratio of phosphorus element to aluminum element in the binder is 6:1, the phosphorus-containing compounds are sodium phosphate and phosphoric acid, and the aluminum-containing compound is aluminum isopropoxide. The content of the binder modifier in the binder is 2.7wt% (based on the total mass of the catalyst dry basis as 100%), the multi-dentate chelating ligand in the binder modifier is an octadentate chelating ligand diethylenetriaminepenta(methylenephosphonic acid), the organic acid is lactic acid, the alcohol is ethanol, the transition metal ion compound is cobalt chloride, the rare earth metal ion compound is samarium chloride, and the molar ratio of cobalt ion to samarium ion is 1:8.

[0128] The preparation method of the above catalytic cracking catalyst is as follows:

[0129] Preparation of matrix slurry:

[0130] After montmorillonite, pseudo-boehmite (peptization index is 25%) and deionized water are mixed and homogenized, a small amount of hydrochloric acid is slowly added, and the slurry temperature is raised and maintained at about 50° C. to acidify and peptize to prepare a matrix slurry.

[0131] Preparation of Binder Modifier:

[0132] S1: The octadentate chelating ligand diethylenetriaminepenta(methylenephosphonic acid) is mixed with a lactic acid solution to prepare a lactic acid solution of a diethylenetriaminepenta(methylenephosphonic acid) multidentate chelating ligand. After mixing evenly, an ethanol solution is added to prepare a diethylenetriaminepenta(methylenephosphonic acid) ligand solution. The molar concentration of the diethylenetriaminepenta(methylenephosphonic acid) is 0.6 mol / L, the concentration of the organic acid in the solution is 20%, and the concentration of the ethanol is 10%.

[0133] S2: Add samarium chloride and cobalt chloride to the lactic acid solution, add ethanol solution after they are completely dissolved, mix well to obtain a mixed metal center ligand precursor solution. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, and the molar concentration of the mixed metal in the precursor solution is 0.15 mol / L

[0134] S3: Add the diethylenetriamine penta(methylenephosphonic acid) ligand solution obtained in S1 and the metal center ligand precursor solution obtained in S2 into a high shear dispersing emulsifier in a volume ratio of 1:1, maintain the temperature at 40°C, add ammonia water to adjust the pH value of the system to 7, and react for 40 minutes to obtain a multi-metal composite chelating modifier solution.

[0135] Preparation of binder:

[0136] Sodium phosphate was mixed with deionized water, stirred at 80°C until completely dissolved, then the pH value of the system was adjusted to 3 with phosphoric acid (concentration 85%), and then aluminum isopropoxide was added in proportion and stirred until completely dissolved, and then the mixed solution was added to a high shear emulsifier, and the reaction temperature was maintained at 80°C for a rapid reaction for 10 minutes, and then a binder modifier was added in proportion, and the reaction was continued at 80°C for 5 minutes to obtain a binder.

[0137] Preparation of catalytic cracking catalyst: at room temperature, add the matrix slurry into a high shear emulsifier, homogenize and add the pre-mixed molecular sieve slurry to obtain a mixed slurry of zeolite molecular sieve and matrix, add the above-mentioned binder and the mixed slurry of zeolite molecular sieve and matrix into the high shear emulsifier, emulsify at high speed for 2 minutes and immediately lead out, spray forming and drying, the spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, the spray tail gas temperature is controlled at 160°C, the obtained material is roasted at 450°C for 1 hour, and then ion exchange is carried out for 0.3 hour with an ammonium bicarbonate salt solution with a pH value of 3.0 to 3.5 to obtain a catalytic cracking catalyst.

[0138] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0139] Comparative Example 1

[0140] The contents of the components and raw materials of the catalytic cracking catalyst provided in this comparative example are the same as those in Example 5, and the only difference from Example 5 is that the binder in this comparative example is aluminum sol commonly used in the industry.

[0141] Preparation of catalytic cracking catalyst: at room temperature, add the matrix slurry into a high shear emulsifier, homogenize and add the pre-mixed molecular sieve slurry to obtain a mixed slurry of zeolite molecular sieve and matrix, add aluminum sol and the mixed slurry of zeolite molecular sieve and matrix into the high shear emulsifier, emulsify at high speed for 2 minutes and immediately discharge, spray-form and dry, spray-form conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, the spray tail gas temperature is controlled at 160°C, the obtained material is calcined at 450°C for 1 hour, and then ion exchange is carried out for 0.3 hour with an ammonium chloride solution with a pH value of 3.0 to 3.5 to obtain a catalytic cracking catalyst.

[0142] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0143] Comparative Example 2

[0144] The contents of the raw materials in the catalytic cracking catalyst and the preparation method of the catalyst provided in this comparative example are the same as those in Example 5. The only difference from Example 5 is that in this comparative example, pseudo-boehmite with a peptization index of 99% is used to replace the pseudo-boehmite with a peptization solubility of 25% in Example 5, and the binder does not contain a binder modifier.

[0145] Specifically, the preparation method of the binder in this comparative example is as follows: sodium phosphate is mixed with deionized water, stirred at 80°C until completely dissolved, then the pH value of the system is adjusted to 3 with phosphoric acid (concentration 85%), and then aluminum isopropoxide is added in proportion and stirred until completely dissolved, and then the mixed solution is added to a high shear emulsifier, and the reaction temperature is maintained at 80°C for rapid reaction for 10 minutes to obtain the binder.

[0146] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0147] Comparative Example 3

[0148] The contents and preparation methods of the components in the catalytic cracking catalyst provided in this comparative example are the same as those in Example 5, and the only difference from Example 5 is that a mixed solution of cobalt chloride and samarium chloride is used in the binder of this comparative example to replace the binder modifier prepared by the octadentate chelating ligand diethylenetriaminepenta(methylenephosphonic acid), lactic acid, ethanol, cobalt chloride and samarium chloride in Example 5.

[0149] Preparation of the binder in this comparative example: Sodium phosphate is mixed with deionized water, stirred at 80°C until completely dissolved, then the pH value of the system is adjusted to 3 with phosphoric acid (concentration 85%), and then aluminum isopropoxide is added in proportion and stirred until completely dissolved, and then the mixed solution is added to a high shear emulsifier, and the reaction temperature is maintained at 80°C for rapid reaction for 10 minutes, and then a mixed aqueous solution of cobalt chloride and samarium chloride is added in proportion, wherein the molar concentration of the mixed metal of cobalt chloride and samarium chloride is 0.15 mol / L, and the molar ratio of cobalt ions to samarium ions is 1:8, and the reaction is continued at 80°C for 5 minutes to obtain the binder.

[0150] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0151] Comparative Example 4

[0152] The contents of the components in the catalytic cracking catalyst provided in this comparative example and the preparation method are the same as those in Example 5. The only difference from Example 5 is that the preparation of the binder and the catalyst in this comparative example is not carried out using a high shear emulsifier, but in a conventional reactor. The specific process is as follows:

[0153] Preparation of matrix slurry: same as in Example 5;

[0154] Preparation of binder modifier: Same as Example 5;

[0155] Preparation of the binder: Sodium phosphate is mixed with deionized water, stirred at 80°C until completely dissolved, then the pH value of the system is adjusted to 3 with phosphoric acid (concentration 85%), and then aluminum isopropoxide is added in proportion and stirred until completely dissolved, and then the mixed solution is added to a stirred reactor, and the reaction temperature is maintained at 80°C for a rapid reaction for 10 minutes, and then a binder modifier is added in proportion, and the reaction is continued at 80°C for 5 minutes to obtain the binder.

[0156] Preparation of catalytic cracking catalyst: at room temperature, add the matrix slurry into a high shear emulsifier, add the pre-mixed molecular sieve slurry after homogenization to obtain a mixed slurry of zeolite molecular sieve and matrix, add the above-mentioned binder and the mixed slurry of zeolite molecular sieve and matrix into a stirred reactor, and immediately discharge it after stirring and emulsifying for 2 minutes, and spray-form and dry it. The spray-form conditions are that the furnace temperature of the spray tower is controlled at 580°C and the spray tail gas temperature is controlled at 160°C. After the obtained material is roasted at 450°C for 1 hour, it is ion-exchanged with an ammonium bicarbonate salt solution with a pH value of 3.0 to 3.5 for 0.3 hour to obtain a catalytic cracking catalyst.

[0157] The physical and chemical properties and catalytic performance of the catalyst are shown in Table 2.

[0158] Comparative Example 5

[0159] The contents of the components in the catalytic cracking catalyst provided in this comparative example and the preparation method are the same as those in Example 5. The only difference from Example 5 is that in this comparative example, the binder modifier is added to the molecular sieve slurry instead of being added to the binder to modify the binder. The specific process is as follows:

[0160] Preparation of the binder: Sodium phosphate was mixed with deionized water, stirred at 80°C until completely dissolved, phosphoric acid (concentration 85%) was added to adjust the pH value of the system to 3, and then aluminum isopropoxide was added in proportion, stirred until completely dissolved, and then the mixture was added to a high shear emulsifier, and the reaction temperature was maintained at 80°C for rapid reaction for 10 minutes to obtain the binder.

[0161] The preparation of the binder modifier is the same as in Example 5.

[0162] Preparation of catalytic cracking catalyst:

[0163] S1: Mix montmorillonite, pseudo-boehmite (peptization index is 25%) and deionized water, homogenize them, slowly add a small amount of hydrochloric acid, raise the temperature and keep the slurry temperature at about 50°C, acidify and peptize, and prepare a matrix slurry.

[0164] S2: Mix the ultra-stable Y-type molecular sieve with deionized water, add the prepared binder modifier after mixing evenly, react for 30 minutes, add it to a high-speed high-shear emulsifier, mix it with the binder and the matrix slurry prepared in S1, and then spray-form and dry it. The spray-forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 450°C for 1 hour, and then ion exchanged with an ammonium bicarbonate salt solution with a pH value of 3.0 to 3.5 for 0.3 hour to obtain a catalytic cracking catalyst.

[0165] Comparative Example 6

[0166] The contents of the components and the preparation method of the catalytic cracking catalyst provided in this comparative example are the same as those in Example 5. The only difference from Example 5 is that the binder modifier in this comparative example is ethylenediaminetetraacetic acid chelated copper and hydroxyethylethylenediaminetriacetic acid chelated lanthanum, rather than the in-situ synthesized multi-metal composite metal chelate. Since it is impossible to find the metal chelates of cobalt and samarium on sale, the metal chelates of copper and lanthanum are used instead. The specific process is as follows:

[0167] Preparation of the binder: Sodium phosphate is mixed with deionized water, stirred at 80°C until completely dissolved, then the system is adjusted to a pH value of 3 with phosphoric acid (concentration 85%), aluminum isopropoxide is added in proportion, stirred until completely dissolved, then the mixed solution is added to a high shear emulsifier, and the reaction temperature is maintained at 80°C for a rapid reaction for 10 minutes, and then a mixed solution of ethylenediaminetetraacetic acid chelated copper and hydroxyethylethylenediaminetriacetic acid chelated lanthanum is added in proportion, the molar ratio of copper ions to lanthanum ions is 3.5:1, and the reaction is continued at 80°C for 5 minutes to obtain the binder.

[0168] Preparation of catalytic cracking catalyst: at room temperature, add the matrix slurry into a high shear emulsifier, homogenize and add the pre-mixed molecular sieve slurry to obtain a mixed slurry of zeolite molecular sieve and matrix, add the above-mentioned binder and the mixed slurry of zeolite molecular sieve and matrix into the high shear emulsifier, emulsify at high speed for 2 minutes and immediately lead out, spray forming and drying, the spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, the spray tail gas temperature is controlled at 160°C, the obtained material is roasted at 450°C for 1 hour, and then ion exchange is carried out for 0.3 hour with an ammonium bicarbonate salt solution with a pH value of 3.0 to 3.5 to obtain a catalytic cracking catalyst.

[0169] The parameters in the above embodiments are specifically shown in Table 1.

[0170] Table 1 Components and contents of catalysts in various examples

[0171]

[0172]

[0173] Note: M / N represents the molar ratio of transition metal ions to rare earth metal ions, P / Al represents the molar ratio of phosphorus in the phosphorus-containing compound in the binder to aluminum in the aluminum-containing compound; except for the solid content, the content of each component in the table is based on the total dry weight of the catalytic cracking catalyst as 100%.

[0174] The physical and chemical properties and reaction performance of the catalysts prepared in the above examples and comparative examples were characterized and evaluated, and the results are listed in Table 2.

[0175] Table 2 Comparison of physical and chemical properties of catalysts

[0176]

[0177]

[0178] Data Analysis:

[0179] It can be seen from the data in the above table that Comparative Example 1 and Example 5 have the same molecular sieve and matrix content. The catalyst prepared by the formula and method of the present invention has a low wear index, a larger pore volume, a smaller thermal collapse rate, and exhibits better anti-wear performance at high temperatures. At the same time, it has a higher micro-reaction activity, indicating that it has better reaction performance.

[0180] It can be seen from Example 5 that compared with Comparative Example 2, the catalyst prepared using pseudo-boehmite with a peptization index of 25% has a higher pore volume, specific surface area and lower thermal collapse rate, as well as better wear resistance, compared with the catalyst prepared using only aluminum phosphate binder (without multimetal chelate).

[0181] Comparison between Comparative Example 3 and Example 5 shows that adding the same amount of transition metal and rare earth metal chelates to the aluminum phosphate binder can significantly improve the wear index, pore volume and thermal collapse rate of the catalyst, while using the same amount of transition metal and rare earth metal inorganic salts has no effect on improving the bonding properties and pore volume of the binder.

[0182] The comparison between Comparative Example 4 and Example 5 shows that, under the same formula, the catalyst prepared by using the high-efficiency shear emulsifier described in the present invention is beneficial to the emulsification of the γ-alumina precursor and the dispersion of the metal chelate, and the prepared catalyst has better strength, specific surface area, thermal collapse index and micro-reaction.

[0183] Comparison between Comparative Example 5 and Example 5 shows that adding the multi-metal chelate to the slurry of the molecular sieve and the matrix greatly weakens the modification effect of the binder.

[0184] The comparison between Comparative Example 6 and Example 5 shows that the catalyst prepared by in-situ preparation of multi-metal chelates has a richer source of raw materials and has better improvements in binder and reactivity.

[0185] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A catalytic cracking catalyst with high thermal wear resistance, characterized in that: The raw materials of the catalytic cracking catalyst include zeolite molecular sieve, matrix and binder, wherein the matrix is ​​composed of a γ-alumina precursor with a peptization index of ≤50% and clay, and the binder includes a phosphorus-containing compound, an aluminum-containing compound and a binder modifier; The binder modifier comprises a multidentate chelating ligand, a metal center ligand, an alcohol and an organic acid, wherein the metal center ligand contains at least two metal ions; The catalytic cracking catalyst is prepared in a high shear emulsifier.

2. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: The multidentate chelating ligand is a bidentate chelating ligand having at least two coordinating atoms, and the coordinating atoms are P, O or N, O; preferably, the multidentate chelating ligand is selected from any one of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediamine tetra (methylene phosphonic acid), diethylenetriamine penta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, bis (1,6-hexamethylenetriamine penta (methylene phosphonic acid), hexamethylenediamine tetra (methylene phosphonic acid), ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid and 1,2-ethylenediamine.

3. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: The metal ions in the metal center ligand are selected from rare earth metal ions and transition metal ions; preferably, the rare earth metal ions are selected from light rare earth metal ions.

4. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 3, characterized in that: The molar ratio of the transition metal ion to the rare earth metal ion is 1:5-10; the molar ratio of the multidentate chelate ligand to the metal ion in the metal center ligand is 2-5:

1.

5. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: The organic acid is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid; The alcohol is selected from C1-C3 monohydric alcohols, preferably one or more of methanol, ethanol and propanol.

6. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: Based on the total mass of the catalytic cracking catalyst on a dry basis being 100%, the content of the binder modifier is 1% to 3%.

7. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: The molar ratio of the phosphorus element in the phosphorus-containing compound to the aluminum element in the aluminum-containing compound is 4 to 10:1, preferably the molar ratio of the phosphorus element in the phosphorus-containing compound to the aluminum element in the aluminum-containing compound is 5 to 8:1; and / or The peptization index of the γ-alumina precursor is 20% to 30%; preferably, the XRD spectrum of the γ-alumina precursor has characteristic peaks at 2θ of 14±1°, 28±1°, 38±1°, and 49±1°; and / or The mass ratio of the γ-alumina precursor to the clay is 1:1-9, preferably 1:3-7.

8. The catalytic cracking catalyst with high thermal wear resistance as claimed in claim 1, characterized in that: Based on the total dry weight of the catalytic cracking catalyst as 100%, the content of the zeolite molecular sieve is 25wt% to 60wt%, preferably 35wt% to 50wt%; the content of the matrix is ​​30wt% to 50wt%; the content of the binder is 10wt% to 25wt%, preferably 15wt% to 20wt%; the solid content of the catalytic cracking catalyst is 35wt% to 60wt%, preferably 40wt% to 50wt%.

9. A method for preparing a catalytic cracking catalyst with high thermal wear resistance according to any one of claims 1 to 8, characterized in that: The steps include: The mixed slurry of the zeolite molecular sieve and the matrix is ​​mixed evenly with the binder in a high shear emulsifier within 3 minutes, spray-formed and dried, calcined, and ion-exchanged to obtain the catalytic cracking catalyst with high thermal wear resistance.

10. The preparation method according to claim 9, characterized in that: The preparation of the binder comprises the following steps: Adding alcohol to the organic acid solution of the multi-dentate chelating ligand and mixing well to obtain a multi-dentate chelating ligand solution; Adding alcohol to the organic acid solution of the metal center ligand and mixing well to obtain a metal center ligand solution; Adding the multi-dentate chelating ligand solution and the metal center ligand solution into a high shear dispersing emulsifier, and adjusting the pH value of the system to 5-8; Obtaining a binder modifier solution; After heating the aqueous solution of the phosphorus-containing compound with a pH value of ≤5, the aluminum-containing compound is added and mixed, and then the mixed solution is added to a high shear emulsifier for reaction, and then the binder modifier solution is added to continue the reaction. After the reaction is completed, the binder is obtained.

Citation Information

Patent Citations

  • Inorganic binder containing phosphorus and aluminum compounds

    CN102847547B

  • Fcc catalyst additive and binder

    CN108025298A

  • Catalytic cracking catalyst containing phosphorus and zeolite and its preparing method

    CN1132897C

  • Catalytic supports with controlled pore properties

    US4407730A

  • Catalytic cracking utilizing a zeolite and aluminum phosphate-containing catalyst

    US5286369A